2020
DOI: 10.1016/j.diabres.2020.108348
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on glycemic control in patients with type 1 diabetes

Abstract: Introduction: The COVID-19 pandemic has forced governments to take exceptional measures to minimize its spread, imposing lockdown policies. The aim of this study was to evaluate the impact of lockdown on type 1 diabetes (T1D) glycemic control. Material and methods: People with T1D using flash glucose monitoring were included. Data from the 14 days before lockdown were compared with data from the last 14 days after 8 weeks of lockdown. Results: A total of 307 patients were included (age 45.8 ± 12.6 years, 50.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
121
2
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 22 publications
(25 reference statements)
15
121
2
4
Order By: Relevance
“…Authors reported BG worsening in Brazil, India, China and African countries [16,31,33,35,36], while the opposite situation was observed in T1D groups in high income countries (HIC). With access to advanced technology, treatment, specialized services and HCPs used to digital health tools, PwD in HIC maintained or even improved their BG level during the pandemic [59,61,72,73,74]. In a study in Spain, time in range of individuals with T1D using glucose sensors increased, in comparison with the pre-pandemic period, from 57.8% to 62.5% [73], and from 55.8% to 58.2%, in Italy [61].…”
Section: Social Inequalities Hinder Effectiveness Of Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors reported BG worsening in Brazil, India, China and African countries [16,31,33,35,36], while the opposite situation was observed in T1D groups in high income countries (HIC). With access to advanced technology, treatment, specialized services and HCPs used to digital health tools, PwD in HIC maintained or even improved their BG level during the pandemic [59,61,72,73,74]. In a study in Spain, time in range of individuals with T1D using glucose sensors increased, in comparison with the pre-pandemic period, from 57.8% to 62.5% [73], and from 55.8% to 58.2%, in Italy [61].…”
Section: Social Inequalities Hinder Effectiveness Of Measuresmentioning
confidence: 99%
“…With access to advanced technology, treatment, specialized services and HCPs used to digital health tools, PwD in HIC maintained or even improved their BG level during the pandemic [59,61,72,73,74]. In a study in Spain, time in range of individuals with T1D using glucose sensors increased, in comparison with the pre-pandemic period, from 57.8% to 62.5% [73], and from 55.8% to 58.2%, in Italy [61]. However, negative consequences of inequalities were also present in HIC [17,51].…”
Section: Social Inequalities Hinder Effectiveness Of Measuresmentioning
confidence: 99%
“…Other studies investigated changes of glucose control in relation to COVID-19 lockdown in children [7] and adults [8][9][10][11][12] with T1D, overall finding either comparable [7,12] or improved [8][9][10][11] glucose variability in these populations. However, unlike other study cohorts, our patients had prelockdown TIR above the optimal range (TIR> 70%).…”
Section: Statisticsmentioning
confidence: 99%
“…Recently, new approaches are being studied to provide new treatments to diabetic patients. Some studies have been conducted to explore COVID-19 lockdown and glycemic control ... Al Agha et al how diabetic patients are dealing with their diabetes during the COVID-19 lockdown; [7][8][9] however, few have been conducted in Saudi Arabia. We aimed to assess how children and adolescents with T1D were coping with their diabetes during the lockdown, and more broadly, to offer the diabetic community better strategies for healthy living in lockdown.…”
mentioning
confidence: 99%